"Fair use is legal use": Copyright negotiations and strategies in the fan-vidding community. (August 2016) - Freund, Katharina
This article explores the complex relationship of a particular community of remix artists, known as vidders, to copyright law. With streaming video capabilities and the widespread popularity of remix culture, the historically underground vidding community has been forced to adapt to new conditions. In response to much existing scholarship, which portrays remixers and fans as victims of an unjust system, this research draws on ethnographic research to reveal community-based strategies used by vidders to mitigate the risks as perceived infringers of copyright. It will discuss vidders' understandings of copyright law in relation to their work, and also their efforts to legitimize fan practices and remix as legal uses of copyrighted material under US law. Rather than being seen as simply victims of an unjust system, this research demonstrates that online communities have worked proactively to understand and respond to perceived copyright threats.